2009
DOI: 10.1111/j.1365-246x.2009.04391.x
|View full text |Cite
|
Sign up to set email alerts
|

Two-station measurement of Rayleigh-wave phase velocities for the Huatung basin, the westernmost Philippine Sea, with OBS: implications for regional tectonics

Abstract: S U M M A R YA broad-band ocean-bottom seismometer (OBS) deployed ∼180 km east of Taiwan provides a first glimpse into the upper mantle beneath the westernmost section of the Philippine Sea or the Huatung basin (HB). We measured interstation phase velocities of Rayleigh waves between the OBS and stations on the eastern coast of Taiwan. The phase velocities show smooth variations from 3.8 to 3.9 km s −1 for periods of 25-40 s. In this short period range, phase velocities are comparable to those characterizing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 41 publications
1
28
0
Order By: Relevance
“…The age of this small basin is highly controversial. Estimates vary from 131 to 119 Ma (Deschamps et al 2000) to 52-43 Ma for the northern part and Early Cretaceous for the southern part (Sibuet et al 2002), to 44-33 Ma (Hilde and Lee, 1984), 42-33 Ma (Doo et al 2015), or even ∼ 30-15 Ma (Kuo et al 2009). Further details and an interesting discussion about this controversy are available in Eakin et al (2015).…”
Section: Oceanic Basins Of the Pspmentioning
confidence: 99%
“…The age of this small basin is highly controversial. Estimates vary from 131 to 119 Ma (Deschamps et al 2000) to 52-43 Ma for the northern part and Early Cretaceous for the southern part (Sibuet et al 2002), to 44-33 Ma (Hilde and Lee, 1984), 42-33 Ma (Doo et al 2015), or even ∼ 30-15 Ma (Kuo et al 2009). Further details and an interesting discussion about this controversy are available in Eakin et al (2015).…”
Section: Oceanic Basins Of the Pspmentioning
confidence: 99%
“…Using the same approach, Sibuet et al (2002) suggested that the HB was formed between C20 and C23 (51-43 Ma). Kuo et al (2009) measured phase velocities of Rayleigh-wave between OBS (broad-band ocean-bottom seismometer) and stations on the eastern coast of Taiwan and proposed that the characteristic of the phase velocities of the HB is comparable to the 15-30 Ma Parece-Vela basin. Hsu et al (1998) also suggests the oceanic crust west of the GR is younger than in the east.…”
Section: Magnetic Featuresmentioning
confidence: 99%
“…Regarding the origin of the Huatung Basin situated in the backside of the arc, many interpretations have been given including an Eocene part of the West Philippine Basin (Hilde and Lee, 1984), an Early Cretaceous trapped piece of an old oceanic basin (Deschamps et al, 2000), a composite back-arc basin with an old (Mesozoic ?) part in the south and an Eocene part in the north (Sibuet et al, 2002) or an Oligo-Miocene oceanic basin (Kuo et al, 2009). Since Hickey-Vargas et al (2008) found an Indian MORB-OIB Hf-Nd isotopic signature and Pb isotope ratios intermediate between Indian and Pacific MORB in the mantle source of the gabbros dredged in the Huatung Basin, it likely corresponds to a trapped piece of early Cretaceous oceanic crust produced at a ridge overlying an Indian-type mantle as proposed by Deschamps et al (2000).…”
Section: Luzon Arc and ''Back-arc * '' Seismic And Petrological Strucmentioning
confidence: 99%